Rudimental: a musical practice tool - Castilho, M.L.C. (2020)
Following the experience of musical teaching, researchers found that often students don’t know how to apply study strategies and be self-proficient. A group of researchers developed an online platform, which intends to optimize the students’ time when playing musical instruments. The platform allows a teacher to monitor students’ work, through the use of data logged during a set of classes and practice sessions. This paper presents the design process and the implications of the tool implementation. The results obtained before and after the use of this platform, by a group of students, are described. Findings show that this platform’s use as a pedagogical practice tool, permitted students to improve their instrumental practice.